Pengaruh Media Sosial Dalam Membangun Karakteristik Mahasiswa KPI FDK UIN-SU - Ezra Muharrifah; Diana Putri Auliyah Rahma; Amelia Putri Daulay (Badan Penerbit STIEPARI Press, 2024)
In the ever-growing digital era, the use of social media has become an important aspect of everyday life, especially among students of the Islamic Communication and Broadcasting Study Program (KPI) at the Faculty of Da'wah and Communication at UIN-SU. The role of social media is not only limited to exchanging information, but also creates a significant impact on students' interpersonal communication patterns, shaping the way they interact, convey messages, and build relationships in cyberspace and in real life. Therefore, further understanding the dynamics of interactions between students and social media can provide a deeper view of the role of social media in shaping students into individuals who are more communicative, connected to their religious identity, and active in campus life.